Pengaruh Digital Marketing dan Daya Tarik terhadap Keputusan Berkunjung (Wisata Paralayang Matantimali) - Sumiansi Sumiansi; Adfiyani Fadjar; Maskuri Sutomo; Sri Wanti (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this research is to determine the impact of digital marketing and attractiveness on visiting decisions (Paragliding tourism in Matantimali Sigi district). Methodology/approach: This study evaluates the hypothesis and gathers quantitative questionnaire data from respondents for inclusion in the quantitative method. It relies on primary data obtained from questionnaires administered to guests at Matantimali paragliding in Sigi Regency. The sample size consisted of 90 respondents. This study used multiple linear regression analysis for data analysis. Results/findings: The research findings show that digital marketing and attractiveness significant impact on encouraging tourists' decisions to visit Paragliding Matantimali, Sigi Regency. Conclusions: Digital marketing and tourist attractions have a significant influence on tourists' decisions to visit Matantimali paragliding, Sigi Regency. Optimizing these two factors can increase tourist visits. Limitations: This research focuses exclusively on Matantimali paragliding tourism in Sigi Regency; it is suggested that further research expand the number of samples and add other variables such as facilities, accessibility, and price for more comprehensive analysis Contribution: The findings of this research are expected to be a strategic basis for Matantimali Paragliding managers in optimizing digital marketing, increasing attractiveness, and designing more effective promotions. Therefore, it is intended to provide a more competitive tourism experience.